The SuperCOSMOS all-sky galaxy catalogue - Peacock, J; Hambly, N; Bilicki, M; MacGillivray, H; Miller, L; Read, M; Tritton, S (Oxford University Press, 2016)
We describe the construction of an all-sky galaxy catalogue, using SuperCOSMOS scans of Schmidt photographic plates from theUKSchmidt Telescope and Second Palomar Observatory Sky Survey. The photographic photometry is calibrated using Sloan Digital Sky Survey data, with results that are linear to 2 per cent or better. All-sky photometric uniformity is achieved by matching plate overlaps and also by requiring homogeneity in optical-to-2MASS colours, yielding zero-points that are uniform to 0.03 mag or better. The typical AB depths achieved are BJ < 21, RF < 19.5 and IN < 18.5, with little difference between hemispheres. In practice, the IN plates are shallower than the BJ and RF plates, so for most purposes we advocate the use of a catalogue selected in these two latter bands. At high Galactic latitudes, this catalogue is approximately 90 per cent complete with 5 per cent stellar contamination; we quantify how the quality degrades towards the Galactic plane. At low latitudes, there are many spurious galaxy candidates resulting from stellar blends: these approximately match the surface density of true galaxies at |b| = 30°. Above this latitude, the catalogue limited in BJ and RF contains in total about 20 million galaxy candidates, of which 75 per cent are real. This contamination can be removed, and the sky coverage extended, by matching with additional data sets. This SuperCOSMOS catalogue has been matched with 2MASS and with WISE, yielding quasiall- sky samples of respectively 1.5 million and 18.5 million galaxies, to median redshifts of 0.08 and 0.20. This legacy data set thus continues to offer a valuable resource for large-angle cosmological investigations.